MEWUJUDKAN LEGITIMASI DEMOKRASI MELALUI PENEGAKAN HUKUM PEMILIHAN UMUM (PEMILU) - Sutarno Sutarno (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
Elections are a way of implementing a democratic system. The availability of legal instruments that guarantee an honest and fair election process is an absolute demand for the democratization process. Everything that destroys the democratic order in order to maintain power is a disease and a challenge that must be faced by the Election Organizer. The legitimacy of democracy must be maintained by enforcing the general election law which is regulated in detail by adopting societal conditions and international standards in order to produce the best product. This is because the most important factor is the implementation of democratic elections through supervision and law enforcement.